DIGITAL TRANSFORMATION AS A STRATEGIC LEVER FOR ENHANCING SUSTAINABLE DEVELOPMENT IN IRAQ: AN ANALYSIS OF REALITY, STRUCTURAL CHALLENGES, AND FUTURE DEVELOPMENT OPPORTUNITIES - Hassan Abdullah Ahmed (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
This research aims to provide a realistic analysis of digital transformation in Iraq during the period 2015-2025 and explore the most important strategic differences for social development. This is achieved by examining the alignment between digital indicators and development indicators, identifying the overarching challenges facing these companies, and anticipating future opportunities for advancement. The research employs a descriptive and analytical approach, relying on data from the Central Statistical Organization, the Central Bank of Iraq, and the United Nations Development Programme, as well as relevant academic literature. The research found a strong correlation between social transformations and digital libraries, manifested in digital contributions to improving financial security, managing government services, and providing access to services and services. However, the impact of digital transformation remains below expectations due to a set of structural challenges, most notably the weakness of the digital infrastructure, the continued dominance of traditional methods in the Iraqi economy, the weakness of local resources, and the limited availability of digital skills. The research concludes that Iraq's success in achieving comprehensive development during this period hinges on establishing an integrated development model for companies based on investment and digital knowledge.